Date seeds (Phoenix dactylifera L.) valorization for boilers in the mediterranean climate - de la Cruz-Lovera, Carmen; Manzano-Agugliaro, Francisco; Salmerón-Manzano, Esther; de la Cruz-Fernández, José Luis; Perea-Moreno, Alberto-Jesus (Sustainability, 2019)
Energy saving is a global priority, as it is helping both energy and environmental sustainability by reducing CO2 emissions. The search for new energy solutions is therefore necessary. In the Mediterranean climate, resources are generally scarce, and all energy sources need to be explored, including biomass from agricultural or industrial waste. There is a clear upward trend in date worldwide production, having doubled its world production in the last 10 years, and this trend is particularly relevant for Mediterranean climate countries, especially in North Africa and nearby countries. This study analyzes the properties associated with the date seed (Phoenix dactylifera L.) to evaluate its suitability and viability as a new biofuel. Specifically, the viability of replacing the existing gas boiler in a university building in the south of Spain with a system of biomass boilers using this biomass was analyzed as a case study. The results reveal that this biomass has HHV values very similar to those of other biomass sources, 19.121 MJ/kg. With the replacement of the gas boiler by a biomass that uses the date seed, a reduction of 95 tons of CO2 per year is obtained and an economic saving of more than 66% is achieved. In short, this work opens new perspectives for the use of this biomass of date seed in boilers and it is an efficient solution for large public buildings such as the buildings of Mediterranean climate universities.
Keywords: date seed; sustainability; biomass boiler; renewable energy; CO2 reduction; energy efficiency; Scopus; JCR